2010
DOI: 10.1182/blood-2009-08-240317
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 controls the neutrophil migratory response to CXCR2 ligands by direct activation of G-CSF–induced CXCR2 expression and via modulation of CXCR2 signal transduction

Abstract: Neutrophil mobilization, the release of neutrophils from the bone marrow reserve into circulating blood, is important to increase peripheral neutrophil amounts during bacterial infections. Granulocyte colony-stimulating factor (G-CSF) and chemokines, such as macrophage-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
118
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 51 publications
9
118
0
Order By: Relevance
“…4,8,25 In addition to well-defined neutrophil chemoattractants such as IL-8, 25 several reports indicate that G-CSF directly promotes neutrophil recruitment to inflammatory sites, including the lung. 26,27 In this context, G-CSF is thought to play several complementary roles, which include augmenting CXCR2-mediated neutrophil chemotaxis, 28 enhancing the mobilization of neutrophils from the BM into the blood, 29 and stimulating BM granulopoiesis. 30 In the present study, we observed that augmented G-CSF levels are associated with high intragraft IL-12 ϩ DC and Th1-cell abundance in rejecting Ext CI lung recipients.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,25 In addition to well-defined neutrophil chemoattractants such as IL-8, 25 several reports indicate that G-CSF directly promotes neutrophil recruitment to inflammatory sites, including the lung. 26,27 In this context, G-CSF is thought to play several complementary roles, which include augmenting CXCR2-mediated neutrophil chemotaxis, 28 enhancing the mobilization of neutrophils from the BM into the blood, 29 and stimulating BM granulopoiesis. 30 In the present study, we observed that augmented G-CSF levels are associated with high intragraft IL-12 ϩ DC and Th1-cell abundance in rejecting Ext CI lung recipients.…”
Section: Discussionmentioning
confidence: 99%
“…It is also suggested that Tregs expressing CCR4 are chemoattracted by CCL22 secreted from tumor cells or tumor-infiltrating macrophages (11). Recently, it was shown that G-CSF mediated CXCR2 expression on neutrophils and their migration (12). The findings of the production of various cytokines and chemokines (e.g., IL-6 and IL-8) by tumor cells (13)(14)(15)(16) or normal cells (17,18) in the tumor microenvironment raised the possibility of their involvement in chemokine receptor expression on Tregs and their migration.…”
mentioning
confidence: 99%
“…No overall expansion in the Gr-1 + BM population is seen (7). As CxCR2 expression correlates positively with Gr-1 expression and neutrophil maturity (11), these data indicate that diabetes inhibits neutrophil maturation, promoting an expansion of the Gr-1 + precursor subset, and that wounding compounds this effect.…”
Section: Impaired Myeloid Maturation Begins In the Bmmentioning
confidence: 69%
“…They home to injury sites after mobilization from the bone marrow (BM), neutralize pathogens early in healing, and promote angiogenesis later in repair (7). Wound recruitment is controlled by the chemokine receptors CCR2 and CxCR2 (8,9), which are expressed by Ly6C + monocytes (10) and Ly6G + granulocytes (11), respectively. Both subsets are required for timely healing, and CCR2 + monocytes play a crucial role in wound angiogenesis (8,9).…”
mentioning
confidence: 99%